A privatização de presídios e sua (in)compatibilidade com o estado democrático de direito: a ressocialização irrefletida - SILVA, José Adaumir Arruda da (Universidade Federal do Pará, 2017)
This work deals with the privatization of prisons and their (in) compatibility with the democratic rule of law, considering the resocialization by the work as the main justification for the transfer of the custody of the stuck of the State to the private sector. Seeks to show that although privatization of prisons is announced as a solution to the ills of the Brazilian prison system and would favor the resocialization of the convict actually is incompatible with the democratic rule of law by violating the dignity of the human person in many respects. To prove this hypothesis, the research have as the referential theoretical: authors who are part of the critical criminology and who understand by the delegitimization of the penal system; the garantismo of Luigi Ferrajoli rejecting the positive special prevention as the finality of the penalty private of liberty. Also reinforces the verification of the hypothesis the field research conducted in Prison Complex of Ribeirao das Neves, Minas Gerais State, pointing neoliberal capitalist aspects of the contract of public-private partnership signed between the Government and the Consortium Managers Prison Associates. The dissertation concludes that privatization of prisons is incompatible with the Democratic Rule of Law, because violates human dignity and the principle of equality; delegates to the particular typical activity of the State; induces semi-slave labor; favors the earnings of companies with exploration prison market; encourages the mass imprisonment, which makes the argument of resocialization to justify the privatization of the imprisonment absolutely false , a mere rant to justify the incarceration industry, which ends up being assimilated thoughtless way by common sense that reaches all the imagery of society.